Ursolic Acid Regulates Cell Cycle and Proliferation in Colon Adenocarcinoma by Suppressing Cyclin B1 - Yang, Minhui; Hu, Changxiao; Cao, Yibo; Liang, Wanling; Yang, Xiangdong; Xiao, Tianbao (Frontiers in Pharmacology, 2021)
Aims: This study aims to investigate the biological function of cyclin B1 (CCNB1) in Colon adenocarcinoma (COAD). Furthermore, the therapeutic effects and potential molecular mechanism of ursolic acid (UA) in COAD cells will also be investigated in vitro. Methods: COAD data were obtained from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) database. Differentially expressed genes (DEGs) were determined with differential analysis. The biological functions of CCNB1 were analyzed through the GeneCards, the Search Tool for the Retrieval of Interacting Genes (STRING) and the Database for Annotation, Visualization and Integrated Discovery database (DAVID). Therapeutic effects of UA on COAD cell lines HCT-116 and SW-480 were analyzed by CCK-8 and high-content screening (HCS) imaging assay. Flow cytometry assays were used to detect cell cycle changes of HCT-116 and SW-480 cells. mRNA and protein expression level were detected by qRT-PCR and Western blotting in HCT-116, SW-480 and normal colon epithelial cells NCM-460. Results: CCNB1 was highly expressed and acted as an oncogene in COAD patients. CCNB1 and its’ interacting genes were significantly enriched in cell cycle pathway. UA effectively inhibited the proliferation and injured COAD cells. In addition, UA arrested cell cycle of COAD cells in S phase. With regard to the molecular mechanism of UA, we demonstrated that UA can significantly down-regulate CCNB1 and its’ interacting genes and proteins, including CDK1, CDC20, CCND1 and CCNA2, which contributed to cell cycle blocking and COAD treatment. Conclusion: Results from this study revealed that UA possesses therapeutic effects on COAD. The anti-COAD activities of UA tightly related to suppression of CCNB1 and its’ interacting targets, which is crucial in abnormal cell cycle process.